Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Return On Asset Pada PT. Bank Syariah Indonesia, Tbk Periode 2021-2022 - Noeridha, Noorsyah Adi (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research aims to examine the influence of Current Ratio and Debt to Equity Ratio on Return on Assets at PT. Bank Syariah Indonesia, Tbk for the 2021-2022 period. The method used in this research is quantitative method. The population in this study is the financial statements of PT. Bank Syariah Indonesia, Tbk. And the sample in this study is two years from 2021 to 2022. The research model used is a multiple regression model. Sampling was conducted using the nonprobability sample method contained in the Annual Report of PT. Bank Syariah Indonesia, Tbk. In this study, the existing variables are independent variables, namely Current Ratio (CR) and Debt to Equity Ratio, the dependent variable is Return On Assets (ROA). The results of the study show that the current ratio and Debt to Equity Ratio do not affect return on assets simultaneously. The current ratio has no effect on return on assets partially Debt to Equity Ratio has no effect on return on assets partially. Keywords: Current Ratio, Debt to Equity Ratio, Return on Aset